2022
DOI: 10.3390/ijms23020801
|View full text |Cite
|
Sign up to set email alerts
|

MiR-320-3p Regulates the Proliferation and Differentiation of Myogenic Progenitor Cells by Modulating Actin Remodeling

Abstract: Skeletal myogenesis is essential for the maintenance of muscle quality and quantity, and impaired myogenesis is intimately associated with muscle wasting diseases. Although microRNA (miRNA) plays a crucial role in myogenesis and relates to muscle wasting in obesity, the molecular targets and roles of miRNAs modulated by saturated fatty acids (SFA) are largely unknown. In the present study, we investigated the role of miR-320-3p on the differentiation of myogenic progenitor cells. Palmitic acid (PA), the most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Several studies have examined the direct effects of PA on cultured myoblasts and myocytes. Similar to the findings of the present study, treatment of myoblasts with PA has been shown to inhibit myogenic cell differentiation and myotube maturation [ 21 , 22 , 39 , 40 ] and reduce type II myosin protein expression [ 41 ]. We further clarified the detailed mechanism by which PA treatment selectively inhibits the expression of specific MHC isoforms at a transcription level during myoblast differentiation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have examined the direct effects of PA on cultured myoblasts and myocytes. Similar to the findings of the present study, treatment of myoblasts with PA has been shown to inhibit myogenic cell differentiation and myotube maturation [ 21 , 22 , 39 , 40 ] and reduce type II myosin protein expression [ 41 ]. We further clarified the detailed mechanism by which PA treatment selectively inhibits the expression of specific MHC isoforms at a transcription level during myoblast differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, PA has been shown to induce endoplasmic reticulum (ER) stress, which in turn triggers programmed cell death via apoptosis [ 19 , 20 ]. PA also regulates the expression of several microRNAs, thereby inhibiting myoblast differentiation and maturation into myofibers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this is the first study which investigates miR‐320‐3p expression in AKI. Previous research on miR‐320‐3p has focused on pulmonary hypertension, ischaemia/reperfusion injury and muscle wasting in obesity 10–12 . In this study, the death group showed greatly higher the levels of serum miR‐320‐3p, NGAL, KIM‐1 and the APACHE II mark than the survival group, suggesting that the levels of serum miR‐320‐3p, NGAL and KIM‐1 are related to the severity of sepsis complicated with AKI, and may take part in the appearance and growth of AKI.…”
Section: Discussionmentioning
confidence: 64%
“…Previous research on miR-320-3p has focused on pulmonary hypertension, ischaemia/reperfusion injury and muscle wasting in obesity. [10][11][12] In this study, the death group showed greatly higher the levels of serum miR-320-3p, NGAL, KIM-1 and the APACHE II mark than the survival group, suggesting that the levels of serum miR-320-3p, NGAL and KIM-1 are related to the severity of sepsis complicated with AKI, and may take part in the appearance and growth of AKI. Similarly, Hu X M et al displayed that serum NGAL and KIM-1 extents were significantly grown in the death group, and the combined detection of the two tests had good predictive value for neonatal renal injury with sepsis at 28d.…”
Section: Discussionmentioning
confidence: 65%
“…More miRNAs have been implicated in muscle differentiation as research has progressed in recent years. MiR-320-3p was discovered to promote Factin accumulation by inhibiting CFL2, activating YAP1, and increasing myoblast proliferation, ultimately compromising myoblast differentiation (19). MiR-22-3p suppresses skeletal muscle cell proliferation while promoting cell differentiation in Hu sheep by targeting IGFBP3 (20).…”
Section: Introductionmentioning
confidence: 99%